Faktor-Faktor Penentu Daya Saing UMKM Agroindustri Tahu Kuning di Jawa Timur: Pendekatan SEM-PLS - Satriya Bayu Aji; Reksa Nanda Prayoga; Agustia Dwi Pamujiati; Nina Lisanty; Kevin Dyo Pamungkas; Wardatul Chamro (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
This study aims to analyze the influence of technological support, supply chain networks, efficiency, entrepreneurial orientation, adaptive capacity, and innovation on the competitiveness of Yellow Tofu Agroindustry MSMEs in East Java. The study uses a quantitative explanatory approach with a Cross Sectional Design. The research sample consisted of 100 MSMEs determined from a population of 133 MSMEs through the Slovin Formula and selected using Proportional Area Random Sampling. Data were collected through observation, questionnaires, interviews, and documentation. Furthermore, the data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4. The results showed that all constructs met the validity and reliability criteria. The structural model has strong explanatory power, with an R-Square value of 0.813 for efficiency; 0.739 for innovation; 0.945 for competitiveness, and 0.078 for SRMR. Efficiency is the strongest direct factor influencing competitiveness, followed by supply chain network innovation, technological support, and adaptive capacity. Entrepreneurial orientation does not directly influence competitiveness, but it does influence it indirectly through innovation. Efficiency has also been shown to mediate the influence of technological support and supply chain networks on competitiveness. These findings confirm that increasing the competitiveness of yellow tofu MSMEs needs to be directed at strengthening operational efficiency, supply chain integration, technology utilization, adaptive capabilities, and measurable business innovation.